Analysis Legal Awareness in Sustainable Finance through the Good Corporate Governance Risk Compliance Framework under POJK No. 51/POJK.03/2017 - Chandra Erick Manaek Pandapotan Lumban Gaol; Tarsisius Murwadji; Beniadi Setiawan (Universitas Islam Sultan Agung, 2026)
The implementation of sustainable finance in Indonesia continues to face a significant gap between regulatory expectations and corporate practices, particularly in the coal mining sector. Despite the Sustainability Report requirement under POJK No. 51/POJK.03/2017, environmental violations and inadequate post-mining reclamation demonstrate that formal compliance may not reflect substantive legal awareness. This study aims to examine the implementation of sustainable finance obligations and assess the legal awareness of major coal mining issuers through the Good Corporate Governance, Risk, and Compliance (GC-GRC) framework. A normative-empirical (socio-legal) approach was employed using hybrid content analysis to triangulate primary data from corporate sustainability reports with secondary data documenting thirty environmental and social violations. The findings reveal persistent greenwashing practices, where formal sustainability disclosures are inconsistent with empirical environmental performance. Most issuers demonstrate an Instrumental Legal Culture, treating compliance primarily as a means to avoid regulatory sanctions rather than as an internalized commitment to ecological justice. The study concludes that strengthening sustainable finance requires not only regulatory compliance but also the transformation of corporate legal culture through an effective GC-GRC framework and stronger institutional enforcement.